MANAGEMENT OF DYSMENORRHOEA WITH MATRA VASTI -A CASE REPORT - S.K.Hemavathi; M.R.Amritha; S.R.Divya Rani; S.Deepthy; J.Divya Sreenath (International Journal of Applied Ayurved Research, 2017)
Dysmenorrhoea is a common gynaecological disorder among females of reproductive age group, as pain during menstruation may incapacitate even day to day activities. In Ayurveda this condition can be correlated to udavarta yoni vyapath with vitiation of vata dosha. The present case report documents, a 24 year old unmarried female of primary dysmenorrhoea, managed with sukumara ghrita matravasti.